Rescue Strategy in Cardiogenic Shock: Emergency Transcatheter Aortic Valve Implantation for Failed Bioprosthetic Valve – Case Report - Ricardas Kundelis; Vilhelmas Bajoras; Sigitas Čėsna; Giedrius Davidavičius (Acta Medica Lituanica)
Background: Transcatheter aortic valve implantation (TAVI) has emerged as an essential therapeutic intervention for patients with severe aortic valve disease, providing a less invasive alternative to traditional surgery, particularly in high-risk individuals. TAVI is also increasingly utilized as a valve-in-valve strategy in cases of a bioprosthetic valve failure. However, data on the efficacy of TAVI in the context of a hemodynamic collapse remain limited. Methods: This report represents a young, high-risk patient with a failed bioprosthetic valve and cardiogenic shock treated successfully with TAVI. Results: Emergency TAVI using a Medtronic Evolut Pro+ device achieved rapid hemodynamic stabilization and favorable post-procedural clinical and functional outcomes. Intermittent complete atrioventricular block necessitated the implantation of a permanent pacemaker. Conclusions: This case highlights the potential of TAVI as a safe and effective intervention in critical clinical scenarios. Emergency TAVI is a viable therapeutic intervention for patients with failed surgical bioprostheses presenting with cardiogenic shock.